The Effect of Corporate Governance on Sustainability Report - Bahrul Mulki Hambali; Estu Widarwati; E Wityasminingsih (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2025)
The purpose of this study is to determine the influence of corporate governance (audit committee and independent commissioners) on sustainability report disclosure. The measurement index used as a reference for sustainability reports in this research is the Global Reporting Initiative (GRI) G4. The population in this research is energy, basic materials and industrial sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period. This research is quantitative research and uses descriptive statistics conducted on companies listed on the IDX. The sample for this research is 31 companies registered on the IDX with a sampling technique, namely purposive sampling, namely with criteria that have consistently published sustainability reports for 2020-2022. The results of this research show that the audit committee has a positive effect on sustainability report disclosure. Meanwhile, independent commissioners have no influence on sustainability report disclosure